Choosing a Markov blanket. (28th May 2020) - Parr, Thomas
Abstract: This commentary focuses upon the relationship between two themes in the target article: the ways in which a Markov blanket may be defined and the role of precision and salience in mediating the interactions between what is internal and external to a system. These each rest upon the different perspectives we might take while "choosing" a Markov blanket.